Evaluation of the structural, thermal, rheological and morphological properties of polyethylene functionalized with a maleinized hyperbranched polyester (2019)
This experimental study was carried out with the aim of establishing and analyzing the thermal, structural, morphological, and rheological properties of a polyethylene functionalized with a maleinized hyperbranched polyester. This area of study has scarcely been reported. It is important to study the properties of this material, since it can be employed as functionalizing agent in blends of low density polyethylene and hydrophilic polymers. In addition, it also may be used as alternative for replacing the importation of polyethylene functionalized with maleic anhydride in our country. Therefore, in this experimental study, dicumyl peroxide was utilized to catalyze a functionalization reaction between low density polyethylene and maleinized hyperbranched polyester. In the experiment, dicumyl peroxide concentrations were maintained at 0.50 wt%, 1.0 wt%, 1.5 wt%, and 2.0 wt%. The resultant material after of the functionalization was characterized by various analytic methods including infrared analysis, contact angle, thermogravimetric analysis, X ray diffraction, rheological analysis and scanning electronic microscopy. The functionalization degree of the polyethylene functionalized with a maleinized hyperbranched increased with the dicumyl peroxide amount and in all cases it was higher than 8 weight percent.